Isolation and typing of canine parvovirus from dogs fecal in some area in Indonesia - E. Raharjo Jusa; G. Mudiarto; M. Aeny Rochman Noor; S. Bahri Siregar; M. Partadiredja (Hemera Zoa, 1991)
Canine parvovirus (CPV) has supopsedly been in Indonesia since 1981, but the isolation of aetiological agent has never been reported. In the present study, isolation and typing of CPV in Indonesia is presented. Out of 180 fecal samples collected from unvaccinated dogs were detected 12 isolated virus by using haemagglutination test after growing the virus in CRFK cell line. Typing the isolates were done with monoclonal antibodies. The results showed that all of the isolates are of "new type".